(untitled) (Experimental biology, 2015)
This paper presents the results of studies of C.lanata Chenopodiaceae family growing in Kazakhstan regions. It was a biological screening. The compоrative analysis of seeds of C.lanata Chenopodiaceae family growing in Kazakhstan regions.